2022
DOI: 10.3390/foods11213412
|View full text |Cite
|
Sign up to set email alerts
|

Towards Substitution of Hexane as Extraction Solvent of Food Products and Ingredients with No Regrets

Abstract: Hexane is a solvent used extensively in the food industry for the extraction of various products such as vegetable oils, fats, flavours, fragrances, colour additives or other bioactive ingredients. As it is classified as a “processing aid”, it does not have to be declared on the label under current legislation. Therefore, although traces of hexane may be found in final products, especially in processed products, its presence is not known to consumers. However, hexane, and in particular the n-hexane isomer, has… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 112 publications
0
23
0
Order By: Relevance
“…Limonene, furthermore, is nearly entirely recovered after each extraction cycle whereas, like in any other natural product extraction carried out with n -hexane, huge losses of the oil-derived solvent in the atmosphere and in the food chain are recorded every year. 44 In closer detail, the vegetable oil and natural product industries use approximately 1.1 million tonnes of hexane annually (650 kt for oilseed extraction and 450 kt for the production of natural extracts) to compensate for solvent losses during processing. 44 Of this, two-thirds (730 kt) are released into the atmosphere, and one-third (370 kt) remain in the oils and natural extracts.…”
Section: Economic Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Limonene, furthermore, is nearly entirely recovered after each extraction cycle whereas, like in any other natural product extraction carried out with n -hexane, huge losses of the oil-derived solvent in the atmosphere and in the food chain are recorded every year. 44 In closer detail, the vegetable oil and natural product industries use approximately 1.1 million tonnes of hexane annually (650 kt for oilseed extraction and 450 kt for the production of natural extracts) to compensate for solvent losses during processing. 44 Of this, two-thirds (730 kt) are released into the atmosphere, and one-third (370 kt) remain in the oils and natural extracts.…”
Section: Economic Aspectsmentioning
confidence: 99%
“…44 Of this, two-thirds (730 kt) are released into the atmosphere, and one-third (370 kt) remain in the oils and natural extracts. 44,45 For example, only in the oil extraction from oilseeds losses amount to about 0.3–0.55 kg hexane per tonne of crushed seeds for soybeans and 0–2–0.7 kg t −1 for rape and sunflower seeds (when using the best available technologies, much more with older plants). 45…”
Section: Economic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limonene, furthermore, is nearly entirely recovered after each extraction cycle whereas, like in any other natural product extraction carried out with n-hexane, about two thirds of the toxic solvent is lost in the atmosphere. 36 In the extraction of food ingredients (including oil extraction from oilseeds) with hexane, indeed, the industry needs slightly more than 1 million t of hexane annually to compensate for solvent losses in the atmosphere during processing. 36 A similar conclusion can be reached for valued Gutta-Percha extracted with limonene from leaves, samara, and bark of Eucommia ulmoides, a tree whose excellent natural rubber chiefly composed of trans-1,4-polyisoprene holds large potential application.…”
Section: Economic Aspectsmentioning
confidence: 99%
“…36 In the extraction of food ingredients (including oil extraction from oilseeds) with hexane, indeed, the industry needs slightly more than 1 million t of hexane annually to compensate for solvent losses in the atmosphere during processing. 36 A similar conclusion can be reached for valued Gutta-Percha extracted with limonene from leaves, samara, and bark of Eucommia ulmoides, a tree whose excellent natural rubber chiefly composed of trans-1,4-polyisoprene holds large potential application. 37 Recently, a joint team in China led by Gu reported that using dlimonene at extraction temperatures ranging from 128 °C (for the samara) through 138 °C (for the leaves), excellent yields of high quality Gutta-Percha ranging 81.14 for the samara through 22.15 mg/g for the leaves and 55.32 mg/g for the bark, are readily obtained.…”
Section: Economic Aspectsmentioning
confidence: 99%